Optimizing the water-ecosystem-food nexus of avocado plantations - Lilli, Maria A.; Efstathiou, Dionissis; Koukianaki, Evangelia A.; Paranychianakis, Nikolaos; Nikolaidis, Nikolaos P. (Frontiers in Water, 2024)
Climate change, food and water security and ecosystem sustainable management are tightly interlinked and require holistic approaches to achieve solutions that do not impact adversely one-another. The objective of this work was to conduct studies, collect data and assess the Water-Ecosystem-Food (WEF) nexus in avocado plantations in the Mediterranean region systematically to minimize the environmental footprint while maximizing the benefits for the farmer and the environment. The study includes two distinct experiments; the first addresses the impact of soil organic amendments addition to optimize the WEF nexus and the second monitors experimentally crop water needs and thus illustrates how irrigation practices aided by technology can reduce substantially water consumption. The results showed that organic amendments addition improves fertility, nutrient sequestration and structure but only had a weak effect on biodiversity by increasing the number of unique species. For the development of an efficient irrigation system it is necessary to determine the radius around the tree, the depth of the roots and the time required for the water to reach the active root zone to determine the amount and duration of irrigation. In this way sufficient water will be added to replenish the soil moisture deficit created due to the evapotranspiration. HYDRUS-1D model was used to simulate soil moisture and the hydrologic budget of an avocado tree located in Koiliaris river basin and confirm the percolation losses to groundwater. The results of this study showed that the actual irrigation needs of avocados in the Mediterranean is less than 2,000 m3/ha which is 75% less than what is recommended and could become the primary measure for the mitigation of climate change impacts especially in semi-arid regions such as the Mediterranean.